2017
DOI: 10.1177/1010428317717983
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hypoxia inducible factor 1 alpha and its clinical significance in esophageal carcinoma: A meta-analysis

Abstract: Many studies have analyzed the relationship between hypoxia inducible factor 1 alpha expression and its relation to differentiation, lymph node metastasis, and other clinicopathological variables of esophageal carcinoma, but the results are still inconsistent. This meta-analysis was carried out to explore hypoxia inducible factor 1 alpha in esophageal carcinoma and its correlation with clinicopathological features and prognosis, in order to provide comprehensive reference for clinic. A total of 18 studies incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Our research was in line with many previous meta-analyses investigating the prognostic significance of HIF-1α in other tumors, such as esophageal carcinoma, 20 oral squamous cell carcinoma, 21 lung cancer, 22 glioma, 41 etc. All these studies had demonstrated that HIF-1α expression was correlated with poor prognosis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our research was in line with many previous meta-analyses investigating the prognostic significance of HIF-1α in other tumors, such as esophageal carcinoma, 20 oral squamous cell carcinoma, 21 lung cancer, 22 glioma, 41 etc. All these studies had demonstrated that HIF-1α expression was correlated with poor prognosis.…”
Section: Discussionsupporting
confidence: 89%
“…It has been reported that expression of HIF-1α promotes tumor cell proliferation, invasion, migration, and resistance to radiotherapy. 18,19 Numerous studies have confirmed that HIF-1α expression is related to poor survival in various cancers, such as esophageal carcinoma, 20 oral squamous cell carcinoma, 21 and lung cancer. 22 However, the prognostic value of HIF-1α expression in NPC has not been clearly elucidated until now.…”
Section: Introductionmentioning
confidence: 99%
“…In EC, high HIF-1α levels have been correlated with tumor depth of invasion, differentiation, lymphatic permeation and metastization [34]. Accordingly, HIF-1α and hypoxic-associated biomarkers, such as carbonic anhydrase IX (CAIX) and glucose transporter 1 (GLUT-1) were strongly associated with worse prognosis and poor treatment outcome of EC patient’s [13,35,36].…”
Section: Biological Basis Of Cancer Radiation Therapymentioning
confidence: 99%
“…In summary, overexpression of HIF-1 can be produced for EC through a variety of regulatory mechanisms and is closely related to a variety of adverse prognostic factors such as tumor invasion depth, lymph node metastasis, and resistance to chemoradiation. 60 , 61 However, some studies have shown that HIF-1α has different effects on the prognosis of ESCC and EAC, respectively. 62 This suggested that more detailed and precise researches were required on different cell and molecular subtypes.…”
Section: Introductionmentioning
confidence: 99%